Obstructive Pseudotumor of Tuberculosis in a Young Woman: A Rare Presentation - Seyyed Reza Fatemi; M. Ghobakhlou; L. Alizadeh (Case Reports in Gastrointestinal Medicine)
Retroperitoneal pseudotumor is an extremely rare presentation of extrapulmonary tuberculosis. The diagnosis of this paucibacillary disease is difficult which is usually misdiagnosed as a malignant tumor. High index of suspicion is required for early diagnosis and treatment of retroperitoneal pseudotumor which can affect prognosis of this disease. Because of its rarity and difficult diagnosis, we report an 18-year-old immunocompetent girl who presented with abdominal pain and vomiting. Upper endoscopy showed an exudative mass between the second and third parts of duodenum. Abdominal computed tomography (CT) revealed a large retroperitoneal mass with extension into small bowel. Exploratory laparotomy and histopathological examination of tissue showed calcified granuloma. Ziehl-Neelsen staining and PCR confirmed the tuberculosis. The patient was successfully treated with standard antituberculosis therapy.